Local dynamics of topological magnetic defects in the itinerant helimagnet FeGe - A. Dussaux (Nature Portfolio, 2016)
Topological defects may strongly influence the evolution of a materials' micromagnetic structure whilst their manipulation forms the basis for emerging technological concepts. Here, the authors study the depinning and motion of magnetic edge dislocations in the domain structure of helimagnetic FeGe.